Keeping Up with the Times: The Gains and Risks of Utilising Technology to BetterRefugee Lives - Sreyashi Bose (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Technology is an impartial and neutral entity. It serves to make complex tasks easier, more efficient, as well speeds up the process of carrying them out. It can be used to bring down the margin for manual error. There are many advantages and certain disadvantages of utilising technology as a means to manage and improve life chances of asylum seekers and refugees. It can be used to empower as well as surveil and/or discriminate. Technology ought to be used for good, that is, its usage ought to promote refugee justice as well asaccess to human rights.Hence, there is a need for a humanistic approach towards the utilisation of technology in matters pertaining to asylum seekers, refugees and the global refugee crisis.